The Whole Community Development in Supporting Children's Literacy in Rural Areas: Community and Parents’ Participation to Foster Children’s Literacy in Rural Areas - Adhimas Wahyu Agung Wijaya; Ayu Siantoro; Melliana Layuk (Pusbindiklatren Bappenas, 2022)
Indonesia was ranked 72nd out of 77 countries in reading assessment based on Programme for International Students Assessment (PISA). Through the National Literacy Movement, the Indonesian government attempt to increase children's reading proficiency, which is also an indicator of SDG 4.1.1. This study explores the important roles of the parents and community in improving children's literacy competencies. This study used a qualitative approach and collected both primary and secondary data. The findings highlighted that parents supporting children's literacy could improve children's reading interest and early-phase of reading competencies through the availability of reading corners and home-based literacy activities. There were 300 parents supporting children's literacy activities and 73 community facilitators facilitating 20 village reading clubs. The village government also supported the sustainability of the reading club by providing incentives for the facilitators and developing the infrastructure through village fund allocation.